Fruit and vegetable consumption, leisure-time physical activity and binge drinking in Belo Horizonte, Brazil, according to the Health Vulnerability Index - Laís Santos de Magalhães Cardoso; Crizian Saar Gomes; Alexandra Dias Moreira; Regina Tomie Ivata Bernal; Antonio Luiz Pinho Ribeiro; Deborah Carvalho Malta
ABSTRACT: Objective: To estimate the prevalence of fruit and vegetable consumption, practice of leisure time physical activity (LTPA) and binge drinking for small areas of Belo Horizonte, Minas Gerais. Methods: Ecological study conducted with data from the Surveillance System for Risk and Protection Factors for Noncommunicable Diseases by Telephone Survey (Sistema de Vigilância de Fatores de Risco e Proteção para Doenças Crônicas por Inquérito Telefônico - Vigitel). The prevalence of risk and protection factors from 2006 to 2013 were estimated and the 95% confidence intervals calculated. "Small areas" corresponded to the municipality division into four strata of health risk classification given by the Health Vulnerability Index 2012 (Índice de Vulnerabilidade à Saúde - IVS). Results: The mean prevalences for the period were: about 42% of regular intake of fruit and vegetable, 34.7% of leisure time activity and 20.4% of binge drinking. The prevalence of fruit and vegetable consumption was higher in low-risk areas (58.5%; 95%CI 56.8 - 60.2) and lower in very high-risk areas (32.3%; 95%CI 27.7 - 36.9). The practice of LTPA was higher in low-risk areas (40.8%; 95%CI 38.9 - 42.8) and lower in very high risk (25.2%; 95%CI 20.6 - 29.9). Binge drinking was higher in low-risk areas (22.9%; 95%CI 21.7 - 24.2) compared to very high-risk areas (14.3%; 95%CI 11.4 - 17.3). Conclusion: It was identified a gradient in the distribution of risk and protection factors for noncommunicable diseases in Belo Horizonte according to the risk classification. This information can support programs aimed at reducing health inequalities, especially in the most vulnerable areas.